Important determinants of anaerobic running performance in male athletes and non-athletes - Nummela, A.; Mero, A.; Stray-Gundersen, J.; Rusko, H. (International Journal of Sports Medicine, 1996)
The purpose of this study was to investigate the importance of selected metabolic and neuromuscular determinants as predictors of anaerobic running performance. The subjects were male 400-m runners (n = 21), middle- (n = 8) and long-distance runners (n = 11), power athletes (n = 14) and physically active men (n = 34). Maximal power (Pmax), peak blood lactate concentration (peak BLa), power at 10 mM blood lactate level (P10mM), height (CMJrest) and percentage decrease (CMJdecrease) of the counter-movement jump were determined by the maximal anaerobic running test (MART). In addition, maximal oxygen uptake (VO2max) was determined on a treadmill and maximal running velocity (V30m) was measured by the 30-m speed test on a track. Stepwise regression analysis revealed that V30m, P10mM and peak BLa accounted for 92% (P < 0.001) of the variation in Pmax. Regression analysis showed also that V30m, P10mM and delta P (the difference between Pmax and VO2max) were the most important determinants of the 400-m run on a track within a homogeneous group of 400-m runners. The middle-distance and 400-m runners had higher Pmax and P10mM than the long-distance and control group (p < 0.05). The 400-m runners had superior V30m and delta P than the other groups. Furthermore, the 400-m runners and power athletes had higher peak BLa than the long-distance and control group (p < 0.05). The present findings showed that V30m, P10mM and peak BLa determined by the 30-m speed test and the MART were the most important components of anaerobic work capacity. These determinants could be used to explain the differences in anaerobic work capacity between various sport groups as well as between different athletes.